Xylan, Xylooligosaccharides, and Aromatic Structures With Antioxidant Activity Released by Xylanase Treatment of Alkaline-Sulfite–Pretreated Sugarcane Bagasse - Silva, Verônica Távilla F.; Ruschoni, Uirajá C. M.; Ferraz, André; Milagres, Adriane M. F. (Frontiers in Bioengineering and Biotechnology, 2022)
Xylanase enzymes are useful to fractionate plant biomass, producing xylan, xylooligosaccharides (XOS), and antioxidant-derived XOS. In a biorefinery, pretreated biomass can be digested with xylanase prior to cellulose saccharification, enhancing the product portfolio in the process. With this vision, this study highlighted a wide range of new products attainable from alkaline-sulfite–pretreated sugarcane bagasse by treatments with endo-xylanase under controlled conditions. The developed process provided a crude extract corresponding to 29.7% (w/w) of pretreated sugarcane bagasse. The crude extract included a relatively polymeric glucuronoarabinoxylan fraction, DP2-DP6 xylooligosaccharides, and aromatic compounds. The enzymatically produced extract was fractionated with increasing ethanol concentrations [up to 90% (v/v)], providing precipitation of varied polymeric xylan fractions (48% (w/w) of the crude extract) with average molar masses ranging from 28 kDa to 3.6 kDa. The fraction soluble in 90% ethanol was subjected to adsorption on 4% (w/v) activated charcoal and eluted with an ethanol gradient from 10% to 70% (v/v), thus providing xylooligosaccharides and aromatic fractions. Most of the xylooligosaccharides (74% of the eluted sugars) were washed out in 10%–30% ethanol. DP2 and DP3 structures predominated in the 10% ethanol fraction, while DP5 structures were significantly enriched in the 30% ethanol fraction. Higher ethanol concentrations desorbed xylooligosaccharides associated with higher amounts of aromatic compounds. Total aromatics, phenolic structures, and p-hydroxycinnamates predominated in the fractions desorbed with 60% and 70% ethanol. The antioxidant activity of produced fractions correlated with their phenolic contents. Compiled results indicate that a wide variety of products can be prepared from pretreated biomass using xylanase-aided extraction procedures. Recovered fractions presented different features and specific application prospects. Beyond polymeric xylan with low lignin contamination, xylooligosaccharides or even lignin-carbohydrate complexes with antioxidant activity can be included in the biorefinery portfolio based on the currently developed fractionation studies.